Increased catabolic rate of low density lipoproteins in humans with cholesteryl ester transfer protein deficiency. - Ikewaki, K (1995)
The cholesteryl ester transfer protein (CETP) transfers lipids among lipoprotein particles and plays a central role in lipoprotein metabolism. Humans with genetic deficiency of CETP have both elevated HDL cholesterol and apolipoprotein A-I concentrations as well as decreased LDL cholesterol and apolipoprotein B levels. The present study was undertaken to elucidate the metabolic basis for the decreased LDL cholesterol and apo B levels in CETP deficiency. We conducted a series of in vivo apo B kinetic studies in tow unrelated homozygotes with CETP deficiency and in control subjects. A primed constant infusion of stable isotopically labeled phenylalanine was administered to the two CETP deficient subjects and control subjects and apo B kinetic parameters in VLDL, intermediate density lipoproteins, and LDL were obtained by using a multicompartmental model. The fractional catabolic rates (FCR) of LDL apo B were significantly increased in the CETP-deficient subjects (0.56 and 0.75/d) compared with the controls (mean FCR of 0.39/d). Furthermore, the production rates of apo B in VLDL and intermediate density lipoprotein were decreased by 55% and 81%, respectively, in CETP deficiency compared with the controls. In conclusion, CETP-deficient subjects were demonstrated to have substantially increased catabolic rates of LDL apo B as the primary metabolic basis for the low plasma levels of LDL apo B. This result indicates that the LDL receptor pathway may be up-regulated in CETP deficiency.